REKAYASA MESIN PENGUPAS KULIT BUAH KOPI JENIS ROBUSTA MODEL TEP-JLL 2015 DI KABUPATEN TANA TORAJA - Langi, Jois Limbong; Ludong, Daniel P. M.; Lengkey, Lady C. Ch. E. (Jurnal Teknologi Pertanian (Agricultural Technology Journal, 2020)
ABSTRACTÂ The objective of this research was to design a pulper machine model TEP-JLL 2015 for fresh coffee robusta used in rural areas of Tana Toraja district. The machine was designed based on the analysis of physical characteristics of Robusta Tana Toraja coffee and literature study. The analysis result of physical characteristics showed the average length, thickness width was 12.494 mm, 12.802 mm, 10.687 mm, respectively, and the bulk density was 1,115 kg/m3. The theoretical hopper capacity of this machine was 3.7687 kg. Assuming the cylinder speed was 111.594 rpm with an effective distance setting system or flawed setting of 1.2 cm, the theoretical capacity of this pulper machine was 380.62 kg/hour.Â Keywords: fresh Robusta coffee fruit, pulper machine